Socio-Economic Impact Of Palm Oil Land Conversion To Paddy - Timbul Rasoki; Ana Nurmalia; Lina asnamawati (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2020)
In recent years there has been a change in the function ofoil palm plantations to rice. About 370 hectares of oil palmand swamp plantations in Mukomuko District, Bengkulu,were converted into new rice fields. This research aims toexamine the social and economic impacts of landconversion. The location selection was done purposivelyand the respondent determination was done by using thesolvin method, which resulted in 181 respondents. For dataanalysis using qualitative and quantitative methods. Theresearch results explain the social impact of farmersgathering in the fields more frequently at planting,fertilizing, spraying pests, and at harvest time. Farmers whowere previously very consumptive, especially when theprice of palm oil increased and experienced difficultieswhen the price of fresh fruit bunches fell, are now morecareful in financial development. The environment aroundthe mainland is now more beautiful and the air quality isgetting better. As well as more frequent deliberationsrelated to policies and counseling on paddy farming. Theeconomic impact of paddy farming generates an income ofRp. 36,151,207 / field / hectare / year while oil palmfarming is Rp. 28,308,303 / agriculture / hectare / year.